The poor in the book of Psalms and in Yoruba tradition - Adamo, David Tuesday (Old Testament essays, 2014)
It is an indisputable fact that poverty is the greatest known enemy of humankind. The richest one percent of the world's population controls forty percent of the world, and the poorest fifty percent of the population controls a mere one percent of the world wealth. It has also been established that about 68 percent of the Nigerian population live in abject poverty. During the OT period, poor people were present and were well known. This is the reason why there was legislation to protect them. Terminologies for the poor in the OT are both diverse and problematic. The OT writers use most often, the following vocabularies for the poor: ʾeviykh, dal, ʿniy, and ʿnz. These terms with others are used in the book of Psalms. The purpose of this article is to examine the vocabularies relating to the poor in the book of Psalms and how these vocabularies demonstrate to have various meanings that differ from the traditional meaning already recognised by many scholars. It will also examine the terms used for the poor and poverty in Yoruba religion and culture. The understanding of the polysemiotic nature of these terms will help not only in translating properly the book of Psalms, but also in the construction of a theology of Psalms. Understanding the concept of the poor in the OT and Yoruba tradition can also be regarded as a preparation for Christianity in Africa because of the similarities and differences between the two traditions.